2021
DOI: 10.1177/08884064211001453
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Reality Simulation With Preservice Teacher Candidates: A Conceptual Replication

Abstract: Given the critical importance of discrete instructional practices in special education, teacher candidates must be prepared to implement them upon entering the classroom. In preservice teacher education programs, field placements and clinical experiences rarely provide enough opportunities for preservice teachers to gain the proficiency needed to provide effective instruction. In this study, a randomized control research design was used to investigate the effects of a mixed-reality simulation experience compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 25 publications
3
42
0
Order By: Relevance
“…This would also possibly reduce the nervousness that may be associated with being observed by peers, educators and researchers. Walters et al, ( 2021 ) who conducted a pretest-posttest control group study also found that students who practised in the simulation were more nervous before the session in comparison to traditional role-plays. However, the students showed less worry over subsequent sessions (Bautista & Boone, 2015 ; Walters et al, 2021 ) given the benefits of repeated practice.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This would also possibly reduce the nervousness that may be associated with being observed by peers, educators and researchers. Walters et al, ( 2021 ) who conducted a pretest-posttest control group study also found that students who practised in the simulation were more nervous before the session in comparison to traditional role-plays. However, the students showed less worry over subsequent sessions (Bautista & Boone, 2015 ; Walters et al, 2021 ) given the benefits of repeated practice.…”
Section: Discussionmentioning
confidence: 98%
“…Walters et al, ( 2021 ) who conducted a pretest-posttest control group study also found that students who practised in the simulation were more nervous before the session in comparison to traditional role-plays. However, the students showed less worry over subsequent sessions (Bautista & Boone, 2015 ; Walters et al, 2021 ) given the benefits of repeated practice. While having additional practice sessions would be beneficial, one major barrier to the integration of SBL in teacher education is the high cost of the simulation including the cost of the interactor.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies using the MRS with PSTs have suggested that future studies investigate the length and frequency of experiences needed for participants to produce desired results (Driver et al, 2018; Ely et al, 2018). Our work builds on Walters et al (2021) who conducted a conceptual replication of Vince Garland et al (2016). In the Vince Garland et al (2016) study, participants completed at least 10 simulations on the system of least prompts, whereas the participants Walters et al (2021) only completed two simulations.…”
Section: Discussionmentioning
confidence: 99%